Material Properties - Short Circuit Current Correlations in Quantum Dot Solar Cell - Saifful Kamaluddin, Muzakir; Rajan, Jose (2014)
Quantum dots (QDs) semiconductor of size below its exciton Bohr radius shows fascinating effect of quantum confinement i.e., multiple exciton generation (MEG) upon absorption of single photon with sufficient energy. However despite of the remarkable properties, application of QDs for replacement of dye molecules as light absorber in quantum dot solar cell (QDSC) is still doubtful due to inferior power conversion efficiency (~8.6%) in comparison with the dye-sensitized solar cell (DSSC) (~13%). In order to study the drawback that arises from the light absorber, three QDs were employed for QDSC fabrication viz., CdSe, CdTe and CuInS2; layered onto TiO2 photoelectrode by direct attachment, ligandâfunctionalization and pasteâlayering. Additionally, Z907âbased DSSC was fabricated in order to strengthen the conclusion on the correlation between absorption cross-section of fluorophore and the short circuit current of cell. Five efficiency-affecting parameters are studied i.e., (i) ligand usage, (ii) QDs size distribution, (iii) redox potential of electrolyte, (iv) electronic stability of QDs and (v) absorption cross-section by electrochemical measurements, absorption spectroscopy, photoluminescence spectroscopy and quantum chemical ab-initio calculations. Significant setbacks were observed, i.e., (i) inefficient electron injection through ligand, (ii) unnecessary self-injection from small to big cluster of QDs, (iii) inefficient electron replenishment at HOMOQDs by electrolyte, (iv) non-uniform and uneven excited-state electron distribution of QDs cluster that leads to inefficient electron injection from LUMOQDs to LUMOphotoelectrode and (v) low absorption cross-section than that of Z907 dye.